Association of the manganese superoxide dismutase gene Ala–9Val polymorphism with age of smoking initiation in male schizophrenia smokers. Issue 2 (6th November 2015) - Zhang, Xiang Yang; Rao, Wen‐Wang; Yu, Qiong; Yu, Yaqin; Kou, Changgui; Tan, Yun‐Long; Chen, Da‐Chun; Zuo, Lingjun; Luo, Xiangguang; Soares, Jair C.
Abstract : Schizophrenia patients exhibit higher smoking rates than the general population. A growing body of evidence suggests that cigarette smoke impairs the antioxidant defense mechanisms, leading to oxidative damage. Manganese superoxide dismutase (MnSOD) is the major antioxidant in the mitochondria, catalyzing the metabolism of superoxide radicals to form hydrogen peroxide. Since the identification of a well‐characterized functional polymorphism, Ala–9Val of MnSOD, a number of studies have evaluated the association between Val–9Ala and schizophrenia or cancer. In this study, we hypothesized that the functional polymorphism of MnSOD Ala–9Val was associated with smoking in patients with schizophrenia. This polymorphism was genotyped in 666 chronic male schizophrenia patients (smoker/never‐smoker = 507/159) and 660 male controls (smoker/never‐smoker = 360/300) using a case–control design. The cigarettes smoked per day (CPD) and smoking behaviors were evaluated by clinician‐administered questionnaires and the Fagerstrom Test for Nicotine Dependence (FTND). The results showed no significant differences in MnSOD Ala–9Val genotype and allele distributions between the patients and healthy controls or between smokers and never‐smokers in either patients or healthy controls alone. The smokers with the Ala allele started smoking significantly earlier (19.9 ± 5.8 vs. 21.7 ± 6.5 years, P = 0.005) only in patients. These results suggest that the MnSOD Ala–9Val polymorphism may not influence smoking status in a Chinese male schizophrenia population, but may influence the age at which smoking is started among schizophrenia smokers. © 2015 Wiley Periodicals, Inc.